Local knowledge of inhabitants of the Pantanal’s communities of São Pedro de Joselândia and Barra do Piraim (Mato Grosso, Brazil) concerning Pantanal birds - Oliveira Júnior, Samuel Borges de; Sato, Michèle (SITIENTIBUS série Ciências Biológicas, 2007)
Local communities posses vast knowledge on the environment in which they live. Knowledge is passed from generation to generation and contributes for the development of their culture, being able to be used in the construction of alternatives for conservation and management of the local natural resources. When conservation areas are created, human settlements are generally considered inadequate to remain in the environments where they have been living, which contributes for the loss of local knowledge. This article aims at reviewing the importance of this knowledge by investigating the inhabitants’ perception of two Pantanal communities, São Pedro de Joselândia and Barra do Piraim (Mato Grosso State) in what concerns the birds of the region. Data were obtained by means of open-ended interviews and participant observation carried out with 29 individuals. Results show that traditional knowledge on birds is coherent with the academic knowledge. It is important to record and to conserve this set of local knowledge, since it has direct implications in the management and conservation of the Pantanal bird species.